2003
DOI: 10.2139/ssrn.444200
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Foreign Currency Hedging by UK Non-Financial Firms

Abstract: For 366 large non-financial U.K. firms, this paper reports the factors that are important in determining their decision to hedge foreign currency exposure. The results provide strong evidence of a relationship between expected financial distress costs and the foreign currency hedging decision and more significantly the foreign currency only hedging decision. These findings seem stronger than those found in similar studies using U.S. data. The paper argues that this might be due to the fact that several U.S. st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
14

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 34 publications
2
13
1
14
Order By: Relevance
“…Also consistent with Graham and Rogers (2000), our evidence rejects both hypothesis of reducing costs of underinvestment and hypothesis of tax loss reduction. Our results are in sharp contrast to Judge and Clark (2003), which suggests that the UK evidence strongly supports most of the hypotheses for hedging and non-hedging firms listed in the London Stock Exchange.…”
Section: Multivariate Testssupporting
confidence: 56%
See 2 more Smart Citations
“…Also consistent with Graham and Rogers (2000), our evidence rejects both hypothesis of reducing costs of underinvestment and hypothesis of tax loss reduction. Our results are in sharp contrast to Judge and Clark (2003), which suggests that the UK evidence strongly supports most of the hypotheses for hedging and non-hedging firms listed in the London Stock Exchange.…”
Section: Multivariate Testssupporting
confidence: 56%
“…These are the price-earnings ratio, the market-to-book value of equity ratio, research and development expenditure deflated by total sales and capital expenditure deflated by total sales. 3 We use the natural log of total assets to measure firm size (see Judge and Clark, 2003). 4 (iv) In order to test hypothesis that the currency policy and other potential important determinants of hedging specific for the non-financial firms in HK, this paper employs a series of dummy variables to characterise firms listed in HK.…”
Section: Hypotheses On Foreign Exchange Risk Hedgingmentioning
confidence: 99%
See 1 more Smart Citation
“…While for example Nance, Smith, and Smithson (1993) and Sprčić (2008a) did not find evidence supporting the financial distress argument, other studies found evidence that firms with lower liquidity and higher leverage are more likely to use derivatives. Among others following studies have found evidence, Dolde (1995), Mian (1996), Fok, Carroll, and Chiou (1997), Goldberg, Godwin Kim Tritschler, and Myung-Sun (1998) and Haushalter (2000), Judge (2002), Fehle and Tsyplakov (2005), Singh and Upneja (2008), Afza andAlam (2011), Adam, Fernando, andSalas (2015) and Judge (2015).…”
Section: Rationale For Corporate Hedgingmentioning
confidence: 90%
“…Even though the theoretical debate about financial distress costs is entrenched in the study of capital structure [14], the potential contribution of the study goes beyond capital structure literature. Financial distress costs were found to be a relevant factor for many financing decisions [15], such as in determining the optimal capital structure [16], demand for conventional and Islamic insurance [17], corporate hedging practices [18,19] and trade receivables policy [20]. This is further supported by the recent study conducted by [21].…”
Section: Introductionmentioning
confidence: 88%